2017
DOI: 10.4143/crt.2015.310
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Thyroid Cancer: A Hospital-Based Case-Control Study in Korean Adults

Abstract: PurposeAlthough the incidence of thyroid cancer in Korea has rapidly increased over the past decade, few studies have investigated its risk factors. This study examined the risk factors for thyroid cancer in Korean adults.Materials and MethodsThe study design was a hospital-based case-control study. Between August 2002 and December 2011, a total of 802 thyroid cancer cases out of 34,211 patients screened from the Cancer Screenee. Cohort of the National Cancer Center in South Korea were included in the analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
44
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 25 publications
1
44
1
8
Order By: Relevance
“…In our study, most patients were females (87%), and malignant nodules were only associated with females. In the literature, some studies point to a potential risk of thyroid cancer in obese patients [22,23]. In our study, the average BMI in operated men was 25, while women's BMI was 28, and for those with benign histology and those with cancer, it was 31.…”
Section: Discussionmentioning
confidence: 44%
“…In our study, most patients were females (87%), and malignant nodules were only associated with females. In the literature, some studies point to a potential risk of thyroid cancer in obese patients [22,23]. In our study, the average BMI in operated men was 25, while women's BMI was 28, and for those with benign histology and those with cancer, it was 31.…”
Section: Discussionmentioning
confidence: 44%
“…However, there was no significant difference in ionizing radiation exposure, disease multifocality, surgical management or recurrence between the sporadic and familial cancer patients—these patients did not tend to have worse prognosis. Myung et al conducted another hospital‐based case‐control study, with a total of 802 patients with thyroid cancer included, and concluded that females and those with a family history of thyroid cancer had an increased risk of developing thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The SEER data used for this study do not include tobacco information; however, tobacco is a known risk factor for HNC incidence and mortality, and even after treatment for HNC, more than half of HNC survivors continue to smoke . Although HNC survivors who smoke are more likely to die earlier than nonsmokers, studies from the United States and internationally have shown that smoking and alcohol use decreases the risk of developing SPTC . One mechanism of action is the effect of smoking on radiation.…”
Section: Discussionmentioning
confidence: 99%
“…27 Although HNC survivors who smoke are more likely to die earlier than nonsmokers, 27 studies from the United States and internationally have shown that smoking and alcohol use decreases the risk of developing SPTC. [28][29][30] One mechanism of action is the effect of smoking on radiation. Smoking is known to decrease the efficacy of radiation treatment in HNC management.…”
Section: Discussionmentioning
confidence: 99%